2020
DOI: 10.1002/phar.2427
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Therapeutic Options for Chronic Graft‐versus‐Host Disease

Abstract: Despite improvements in prevention and treatment of acute graft‐versus‐host disease (GVHD), chronic GVHD (cGVHD) remains a significant contributor to morbidity and mortality of allogeneic transplant patients. Chronic GVHD remains a leading cause of late complications posttransplant and is impacted by donor‐, patient‐, and transplant‐related (hematopoietic cell transplant [HCT]) factors. Advances in the biological understanding of cGVHD have provided opportunities to improve clinical interventions for preventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 132 publications
(182 reference statements)
0
16
0
Order By: Relevance
“…In most protocols for cGvHD prevention, anti-thymocyte globulin (ATG) is given in various combinations with methotrexate (MTX), cyclosporine A (CsA), tacrolimus, mycophenolate mofetil (MMF) or sirolimus before the HSC transplant. More recently post-transplant cyclophosphamide in various combination with most immunosuppressive drugs, has had a revolutionary impact on the prophylaxis of cGvHD (68). These drugs presumably act by depleting mostly T cells (ATG) and inhibiting activation of lymphocytes T and B cells.…”
Section: Therapy Of Cgvhd Prophylactic Therapies Available For Cgvhd mentioning
confidence: 99%
See 2 more Smart Citations
“…In most protocols for cGvHD prevention, anti-thymocyte globulin (ATG) is given in various combinations with methotrexate (MTX), cyclosporine A (CsA), tacrolimus, mycophenolate mofetil (MMF) or sirolimus before the HSC transplant. More recently post-transplant cyclophosphamide in various combination with most immunosuppressive drugs, has had a revolutionary impact on the prophylaxis of cGvHD (68). These drugs presumably act by depleting mostly T cells (ATG) and inhibiting activation of lymphocytes T and B cells.…”
Section: Therapy Of Cgvhd Prophylactic Therapies Available For Cgvhd mentioning
confidence: 99%
“…Details of the results are therefore awaited. In the last few years, many exploratory clinical trials have been reported with the general perspective of reducing chronic inflammation and auto/ allo B and T cell mediated immunity and results have been reported with a number of different drugs: rituximab which depletes B cells and therefore inhibits the allo-antibody response; ibrutinib, which irreversibly inhibits both Bruton tyrosine kinase (BTK) and IL-2 inducible tyrosine kinase (ITK), thus reducing B and T lymphocytes activation and additionally inhibits BAFF, IL-6, IL-4, and TNF-a production (69); fostamatinib, which specifically blocks the BCR associated SYK kinase; imatinib that inhibits TGFb and PDGFRa signaling, and is therefore potentially active against fibrosis; ruxolitinib, a selective inhibitor of JAK1/2 (see above), low-dose subcutaneous IL-2, that induces an increase in Tregs; proteasome inhibitors (bortezomib), able to inhibit the degradation of IKB (NFKB inhibitor); extracorporeal photopheresis (ECP) with the aim of inducing the apoptosis of lymphocytes and facilitating the differentiation of DCs; others immunosuppressive agents previously reported for the treatment of the acute GvHD (calcineurin inhibitors, mycophenolate mofetil, mTOR inhibitors, pentostatin); finally, KD-025, an oral rho-associated coiled-coil kinase-2 (ROCK2) protein inhibitor is presently under investigation for the treatment of cGvHD (68). The most prevalent steps in the mechanism of action of cGvHD which are targeted by drugs are shown in Figure 2.…”
Section: Standard Therapy For Cgvhdmentioning
confidence: 99%
See 1 more Smart Citation
“…response rates and duration are suboptimal and thus the search to better comprehend GVHD pathophysiology and uncover more efficacious therapeutic management strategies is ongoing. In their companion articles found in this issue, DiMaggio, 5 Gonzalez, and Pidala, 6 provide concise reviews of the current thinking on acute and chronic GVHD with respect to pathophysiology, staging and classification systems, biomarkers, and new agents being evaluated for the prevention and treatment of GVHD. As their reviews demonstrate, large strides have been made in the understanding of this complication with resultant improvements in responses to therapy and, in some cases, even GVHD-free survival, compared with traditional therapies.…”
Section: E D I T O R I a Lmentioning
confidence: 99%
“…4 Characteristics of chronic GVHD are highlighted and described in further detail in a review in this issue of Pharmacotherapy. 5 Severity of acute GVHD is graded from 0 (absent) to IV/D (very severe; Table 1). Considered one of the most common complications following HCT, cumulative incidences of grades II-IV acute GVHD have been reported in 39-63% of HCT recipients; grades III-IV range from 16% to 37%.…”
mentioning
confidence: 99%